Development of IoT Based Aquaponic Monitoring System for Agriculture Application - Muhammad Al Baihaqi Mat Rani; Izanoordina Ahmad (Journal of Engineering Technology, 2022)
Agriculture’s disadvantages include micronutrient imbalance, nitrogen pollution, and eutrophication. Pesticides increase resistance, extinction, biological proliferation, ammonia, algae, and acidity. Aquaculture and agriculture necessitate manual monitoring and management. Humans have a limited amount of time before measuring and regulating it. Water supply in agriculture will be harmed due to population growth, urbanization, and climate change. To improve water management and security, agriculture’s water consumption must be reconsidered. This initiative focuses on aquaponic monitoring. The IoT aquaponics parameters will be monitored through the system design. Besides, the prototype will be tested and validated. The soil moisture sensor indicates the schedule for watering the plants. The indication of Sawi Plant receives enough sunlight is based on the DHT11 temperature sensor. The pH level sensor maintains a constant pH in the tank by feeding hydroponic fertilizers A and B. As a result, the project improves the current manual system, thus, promote this initiative to save money and time.